2011
DOI: 10.1099/mic.0.042564-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine biosynthesis and transport mechanisms are crucial for fitness and pathogenesis of Streptococcus pneumoniae

Abstract: Polyamines such as cadaverine, putrescine and spermidine are polycationic molecules that have pleiotropic effects on cells via their interaction with nucleic acids. Streptococcus pneumoniae (the pneumococcus) is a Gram-positive pathogen capable of causing pneumonia, septicaemia, otitis media and meningitis. Pneumococci have a polyamine transport operon (potABCD) responsible for the binding and transport of putrescine and spermidine, and can synthesize cadaverine and spermidine using their lysine decarboxylase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
116
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 59 publications
5
116
0
1
Order By: Relevance
“…Previous studies showed that ΔspeE and Δcad were severely attenuated in a manner similar to Δ potABCD , in a mouse model of pneumococcal pneumonia18. Polyamine levels are stringently controlled by intracellular synthesis and transport mechanisms in pneumococci1826.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies showed that ΔspeE and Δcad were severely attenuated in a manner similar to Δ potABCD , in a mouse model of pneumococcal pneumonia18. Polyamine levels are stringently controlled by intracellular synthesis and transport mechanisms in pneumococci1826.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in Salmonella enterica sv. typhimurium, polyamines are required for virulence (13); in Legionella pneumophila, intracellular growth is enhanced by polyamines derived from host cells (14), and in Streptococcus pneumoniae, polyamine biosynthetic pathways and the spermidine transporter PotABCD are important for infection (15,16).…”
mentioning
confidence: 99%
“…Another theory suggests that murein hydrolases are released to lyse neighboring noncompetent pneumococcal cells in a fratricidal manner, facilitating genetic exchange between naturally competent pneumococcal populations (39). The effect of spermidine utilization on autolysis demonstrated here may explain the previously characterized importance of polyamine biosynthetic and transport genes for pneumococcal colonization and pneumonia in the murine model of infection (14).…”
Section: Discussionmentioning
confidence: 70%
“…The first gene of this operon (SPD0809 in strain D39 [21]) is annotated as encoding either lysine decarboxylase or arginine decarboxylase (ADC) in different pneumococcal serotypes. It has been suggested that the primary role of this gene product in pneumococci is the decarboxylation of lysine to cadaverine (14). However, given the location of this gene on the pneumococcal chromosome, we hypothesized that it plays an important role in spermidine biosynthesis via arginine decarboxylation.…”
Section: Resultsmentioning
confidence: 96%